Visualizing a homogeneous blend in bulk heterojunction polymer solar cells by analytical electron microscopy - Pfannmöller, Martin; Flügge, Harald; Benner, Gerd; Wacker, Irene; Sommer, Christoph; Hanselmann, Michael; Schmale, Stephan; Schmidt, Hans; Hamprecht, Fred; Rabe, Torsten; Kowalsky, Wolfgang; Schröder, Rasmus R. (Nano letters, 2011)
To increase efficiency of bulk heterojunctions for photovoltaic devices, the functional morphology of active layers has to be understood, requiring visualization and discrimination of materials with very similar characteristics. Here we combine high-resolution spectroscopic imaging using an analytical transmission electron microscope with nonlinear multivariate statistical analysis for classification of multispectral image data. We obtain a visual representation showing homogeneous phases of donor and acceptor, connected by a third composite phase, depending in its extent on the way the heterojunction is fabricated. For the first time we can correlate variations in nanoscale morphology determined by material contrast with measured solar cell efficiency. In particular we visualize a homogeneously blended phase, previously discussed to diminish charge separation in solar cell devices.